The Economic Impact of Deportation Policies on Undocumented Labour-Dependent Industries : A Quantitative Analysis of Democratic and Republican Administrations - Sanchez Vazquez, Gerardo; de Batz de Trenquelléon, Laure Sabine Marie; Taušer, Josef; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2025)
The bachelor thesis analyzes the economic effects of U.S. deportation policies on labor-intensive industries that rely heavily on undocumented workers. Using data from 2006 to 2024, the study examines how changes in immigration enforcement, measured primarily through annual ICE deportation figures, affect employment, real wages, and output in agriculture, construction, and hospitality. These sectors were selected because they consistently exhibit structural labor shortages and a documented dependence on unauthorized labor. The thesis compiles data from ICE, BLS, BEA, USDA, and FRED, constructing time series for each industry and applying first-difference transformations to ensure stationarity. Regression models are then estimated to identify short-run relationships between deportation intensity and sectoral performance, with macroeconomic controls included to account for economy-wide fluctuations. The findings indicate that higher deportation levels are associated with declines in industry employment and, in some cases, reductions in real value added. Wage effects are limited and do not suggest meaningful improvements for native workers. Instead, the results are consistent with tightening labor shortages and production constraints driven by reduced labor supply. Overall, the thesis concludes that aggressive immigration enforcement imposes measurable economic costs on sectors dependent on undocumented labor while offering limited benefits in terms of wage gains or labor market protection.
Vedoucí práce: Laure Sabine Marie de Batz de Trenquelléon
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2026
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2026
Způsob přístupu: Internet
Keywords: international business [obor bakal. práce]; bakalářské práce; bachelor's theses